Answer:
We substitute [tex]x=\frac{-(-1)+/-\sqrt{(-1)^2-4(1)(-2)} }{2(1)}[/tex]
And simplify [tex]x=\frac{1+/-\sqrt{1-4(1)(-2)} }{2}[/tex]
Step-by-step explanation:
First we rearrange the equation -2=-x+x2-4 into standard form of a quadratic [tex]ax^2+bx+c=0[/tex]. This equation becomes [tex]x^2-x-2=0[/tex] where a=1, b=-1, and c=-2.
The formula is:
[tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a}[/tex].
We substitute [tex]x=\frac{-(-1)+/-\sqrt{(-1)^2-4(1)(-2)} }{2(1)}[/tex]
And simplify [tex]x=\frac{1+/-\sqrt{1-4(1)(-2)} }{2}[/tex]
[tex]x=\frac{1+/-\sqrt{1+8} }{2}[/tex]
[tex]x=\frac{1+/-\sqrt{9} }{2}\\x=\frac{1+/-3 }{2}\\x=2,-1[/tex]